Gold and Apes. Des usages du scepticisme dans la philosophie de Robert Boyle - Jean-Pierre Grima-Morales (Revue LISA)
In 1661, when Robert Boyle published The Sceptical Chymist, he was trying to assess the consistency of the works of contemporary chemists, while criticizing the imperfections of their theories. Boyle suggested that another methodical approach was necessary, a method he described in later books as based on rich experimental data and wary of the obsolete Aristotelian or Paracelsian theories. The sceptical approach thus gave him the opportunity to underline the inadequacies of their positions, as Gassendi and Descartes did with the scholastics. But is the category of “constructive or mitigated scepticism” still necessary to define this critical kind of philosophy ? Richard Popkin elaborated it as one of the responses to the general sceptical crisis. But today it seems necessary to incorporate this rhetorical scepticism into the evolution of the Ciceronian rhetoric of the Renaissance as well as into the dynamic propagation of mechanist ideas in Europe. Instead of being specific to the thinkers of the Royal Society, the sceptical approach then becomes a common trend, equally spread on both sides of the Channel. That is why the significance of the use of this modern scepticism in each thinker ought to be specified, particularly in Boyle’s work.